Levels of engineers participative decision-making in Tenaga Nasional Berhad - Hashim, Rahman; Wok, Saodah (Canadian Center of Science and Education, 2015)
Greater chances of participation in the organisational decision-making processes, will allows employees a greater understanding and familiarity with their tasks. The more chances available for expressing ideas and participating in decision-making process, the greater the satisfaction for them. Data were collected from 336 Tenaga Nasional Berhad (TNB) engineers from four regions in Malaysia Peninsula. Descriptive and inferential statistics were employed to answer the objectives and to test the hypothesis of the study. The result shows that, majority of TNB engineers participated in the organisational decision-making process. However, the level of their participation are still considered to be moderate or low. Hence, it is important to have high level of involvement, especially when the respective engineers are involved in generating alternatives, planning processes and evaluating results.